2017
DOI: 10.24093/awej/vol8no2.21
|View full text |Cite
|
Sign up to set email alerts
|

How Do Indonesian Professional English Teachers Develop Their Pedagogical Competence in Teaching Implementation?

Abstract: This article aims to investigate what kinds of Professional Development (PD) activities done by Indonesian professional English teachers in developing their pedagogical competence dealing with teaching implementation as well as to identify how those activities contribute to their competence development. This qualitative study was done in two stages namely subjects selection and investigation on the subjects' professional development for their pedagogical competence in teaching implementation. The criteria of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…The most popular approach to enhancing professionalism is traditional face-to-face teacher professional development (TPD) such as seminars, workshops, and trainings (see Irmawati, Widiati, & Cahyono, 2017;Utami & Prestridge, 2018). This approach, unfortunately, is "designed as mandatory for particular career stages (e.g., the new academic) or voluntary one-off events around a particular topic or innovation" (Dean, Herden-Thew, Delahunty, & Thomas, 2019, p. 50) which limits the freedoms of teachers to choose suitable TPD activities anytime and anywhere.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular approach to enhancing professionalism is traditional face-to-face teacher professional development (TPD) such as seminars, workshops, and trainings (see Irmawati, Widiati, & Cahyono, 2017;Utami & Prestridge, 2018). This approach, unfortunately, is "designed as mandatory for particular career stages (e.g., the new academic) or voluntary one-off events around a particular topic or innovation" (Dean, Herden-Thew, Delahunty, & Thomas, 2019, p. 50) which limits the freedoms of teachers to choose suitable TPD activities anytime and anywhere.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in the Indonesian context, much research on teachers that has been done mostly focuses on experienced teachers and professional teachers who have received teacher certificates (see, e.g., Abdullah, 2015;Amin, 2014;Anugerahwati & Saukah, 2010;Irmawati, Widiati, & Cahyono, 2017;Rido, Nambiar, & Ibrohim, 2016). Abdullah (2015), for example, investigated the influence of English teacher certification program in Indonesia on inservice teacher learning.…”
mentioning
confidence: 99%
“…Earlier, Amin (2014) identified factors that led English teachers to deserving a professional title. Irmawati, et al (2017) reported on various activities undertaken by professional English teachers in improving their pedagogical skills. Anugerahwati and Saukah (2010) and Rido, et al (2016) conducted research similar in purpose, that is, exploring the journey of professional English teachers, but different in contexts, one in general schools and the other in vocational school.…”
mentioning
confidence: 99%
“…Researchers have focused on English teacher professionalism, for instance Kolo (2006), Anugerahwati (2009), Mustofa (2011), Husein (2013), Amin (2013), Priajana (2015) and Irmawati (2017). Kolo (2006), Anugerahwati (2009), Mustofa (2011) and Husein (2013) discussed profile of professional English teachers.…”
Section: Introductionmentioning
confidence: 99%